Effect of 7E Learning Cycle Model on Students’ Academic Achievement in Biology in Secondary Schools in Chesumei Subcounty, Kenya - Cherono , Juliana; Samikwo , Dinah; Kabesa , Stella (African Journal of Education,Science and Technology (AJEST), 2021)
The objective of the study was to compare the effect of 7E Learning Cycle Model and Conventional Instructional Method on students’ academic achievement in Biology. Quasi experimental design was adopted in this study. A sample size of 346 form three students was selected using stratified sampling and simple random sampling techniques. Data collection instrument was Biology Achievement Test. Validity of the instrument was determined by two experts in Biology Education. Test- retest technique was used to determine the reliability of the instrument. A reliability coefficient of 0.83 was obtained. Mean, standard deviation and t-test were used to analyze data. The results were presented using tables. Results of the study revealed that the mean score of the students in the experimental group was higher than those in the control group. The study also found that there was a statistically significant difference between the mean scores of those taught using 7E Learning Cycle Model and those taught using Convectional Instructional Method. The study concluded that 7E Learning Cycle Model has the potential of improving students’ academic achievement. It was therefore recommended that Biology teachers should employ such constructivist approach as 7 E learning cycle model in teaching. In addition, Kenya Institute of Curriculum Development should organize and conduct capacity building on teachers on the adoption of 7E LCM during instruction.